Determination of shear strength of high strength reinforced concrete beams: experimental and numerical approach - Rajesh, Cherukupally; Kumar, Garje Rajesh (Journal of Structural Engineering, 2024)
Shear Strength of concrete is one of the important criteria for the analysis and design of structures as it causes the sudden failure and becomes catastrophic. There were several studies on the behavior of shear strength of concrete beams but still there is a scope for further investigation on High Strength Concrete (HSC) beams. In the present study two grades of reinforced concrete beams with three shear span to depth ratios (a/d) 1, 2 and 3 for each grade were considered. The beams that were cast and tested experimentally were modelled and tested in numerical based software ATENA. In ATENA, for assigning the material for concrete the cementitious2 and cementitious2 user model was considered. The cementitious2 model consists of Euro-code and model-code as default models, both of them were used in the study to determine the shear strength of reinforced concrete beams. In cementitious2 user material model, the compressive stress-strain model can be user defined in which, the GRK Stress-strain model and Mander’s stressstrain model was given as input to find the shear strength of reinforced concrete beams. The shear strength of the test specimens increased with increasing concrete strength for all a/d ratio values. With the increase in a/d ratio from 1 to 3, the shear strength is found to reduce by about 60%. The strains observed in numerical study indicate that the beams have failed in shear which is similar to experimental results. The shear strength obtained using ATENA with various models was compared with the experimental results and it was found that all the shear strength values were in similar behaviour with experimental results.